Ratio between the amplitude of sensory evoked potentials at the wrist in both hands of left-handed subjects. - Martínez, A C (1980)
Maximum sensory conduction velocity, duration and amplitude of the sensory evoked potentials at the wrist on stimulating digits 1, 2, 3 and 5, were determined bilaterally in 21 left-handed subjects with an age range from 6 to 47 years. The amplitude of the sensory evoked potential at the wrist was larger in the right hand. This asymmetry is the reverse of the one previously observed in right-handed infants and adults. It could be physiological and suggests a difference in density of sensory innervation between the two hands. Asymmetry of sensory innervation can be helpful in the study of hand dominance.